COVID-19 and stroke: a case report - Durmuş, Ensar; Güneysu, Fatih (The European Research Journal, 2020)
COVID-19 disease is a worldwide pandemic. Patients present to hospitals with upper and lower respiratory tract symptoms such as cough, fever, shortness of breath, however it can also be encountered with many different clinics. We aimed to share the patient who has COVID-19 and presented with stroke. A 67-year-old female patient presented to the emergency service complaints of mental fog and shortness of breath. She had known lung cancer, hypertension and diabetes. There were no signs compatible with COVID-19 in her history or examination. No feature was detected in her blood tests. Diffuse cerebral infarction was observed in diffusion MRI examination. The patient, whose general condition was poor, was taken into follow up in intensive care unit. On the eighth day of her follow-up, the patient passed away. In places where COVID-19 disease is observed commonly, it would be appropriate for emergency physicians to take COVID-19 disease into consideration in stroke cases.